Pengaruh Jumlah Kunjungan Wisatawan, Tingkat Hunian Hotel, Lama Menginap Wisatawan Terhadap Pertumbuhan Ekonomi Provinsi Kalimantan Selatan - Fadhila, Rafli Safriannur; Noor Rahmini (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
The research tests whether the magnitude is significant simultaneously and the most dominant variable number of tourist visits, hotel occupancy rates, length of stay of tourist to the economic growth of South Kalimantan period 2002-2016. The research data used is secondary data, which collects data through the publication of the Central Statistics Agency of South Kalimantan Province. The technique used in this study is descriptive analysis and multiple linear analysis techniques. Bases on the research obtained results that the number of tourist visits, hotel occupancy rates, and length of stay of tourists simultaneously influences economic growth. The most dominant variable is the number of tourist visits. At the same time, the variable length of stay of tourists is not significant to economic growth. The results of variable testing regression were carried out through SPSS version 20.